Using Markunsen’s Typology as a Starting Point to Examine the Case of the Center for Defense Space and Security Cluster: The State-Anchor Type of Cluster - KYRIAZIS, Vasileios; METAXAS, Theodore (Theoretical and Practical Research in Economic Fields; Vol 14 No 2 (2023): TPREF, Volume XIV, Issue 2(28), Winter 2023DO - 10.14505/tpref.v14.2(28).17, 2023)
Defense is a strategic sector that is closely tied to national security and sovereignty. As such, governments tend to have a strong interest in supporting and developing the defense industry in their countries. This paper aims to investigate and identify to which of the four types of industrial clusters described by Markusen, the Danish Defence Space and Security (CenSec) cluster belongs to. Our initial argument is that CenSec has the characteristics of a state-anchor cluster, because in the defense cluster, the role of government is typically decisive due to the nature of the industry. The analysis will also explore the implications of the type of cluster for policymakers and industry stakeholders in terms of promoting innovation, competitiveness, and economic growth in a broader correlation with the European business and institutional ecosystem.